Nursing Diagnoses for institutionalized elderly: A scoping review (Research, Society and Development, 2025)
Objective: To map the existing literature on the topic, identify and present the main nursing diagnoses for elderly residents in long-term care facilities, using the NANDA-International (2021-2023) nursing classification. Method: A five-step scoping review: identifying the research question; identifying relevant studies to ensure the scope and purpose of the review; screening studies according to predefined criteria; mapping the data; comparing, summarizing and reporting the results, developed based on the recommendations of the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews and the Joanna Briggs Institute. The search was conducted from December 2021 to December 2022 in four databases. Results: 41 articles were included in the review, totaling 78 main Nursing Diagnoses with NANDA-I taxonomy. The most evident domains with the highest number of diagnoses found were: Domain 1. Health Promotion; Domain 2. Nutrition; Domain 3. Elimination and Exchange; Domain 4. Activity/Rest; Domain 5. Perception/Cognition; Domain 11. Safety/Protection; Domain 12. Comfort. Conclusion: This scoping review mapped the existing literature on nursing diagnoses in elderly residents of long-term care facilities, identifying the main diagnoses with the NANDA-I nursing classification, with the most prevalent being in the domains: Health Promotion, Nutrition, Elimination and Exchange, Activity/Rest, Perception/Cognition, Safety/Protection and Comfort, which points to specific care for this population, and may help to improve nursing care, the practical application of the Nursing Process and personalized care.